DIFFERENTIAL SANDWICH THEOREMS FOR SOME SUBCLASS OF ANALYTIC FUNCTIONS ASSOCIATED WITH LINEAR OPERATORS - Shanmuguam, T.N.; Jeyaraman, M.P.; Singaravelu, A. (Journal of the Indonesian Mathematical Society, 2007)
" PDF file"Â DOI :Â http://dx.doi.org/10.22342/jims.13.1.73.39-50